Human papillomavirus infection among sexual partners attending a Sexually Transmitted Disease Clinic in Rio de Janeiro, Brazil - Afonso, L.A. (Associação Brasileira de Divulgação Científica, 2013)
Cervical cancer is a major source of illness and death among women worldwide and genital infection with oncogenic human papillomavirus (HPV) its principal cause. There is evidence of the influence of the male factor in the development of cervical neoplasia. Nevertheless, the pathogenic processes of HPV in men are still poorly understood. It has been observed that different HPV types can be found among couples. The objective of the present study was to investigate HPV infections in female patients (n = 60 females/group) as well as in their sexual partners and to identify the concordance of HPV genotypes among them. By using the polymerase chain reaction, we detected a 95% prevalence of HPV DNA in women with cervical intraepithelial neoplasia (CIN) compared to 18.3% in women with normal cervical epithelium, with a statistically significant difference (P < 0.001). The HPV DNA prevalence was 50% in male partners of women with CIN and 16.6% in partners of healthy women. In the control group (healthy women), only 9 couples were simultaneously infected with HPV, and only 22.2% of them had the same virus type, showing a weak agreement rate (kappa index = 0.2). Finally, we observed that HPV DNA was present in both partners in 30 couples if the women had CIN, and among them, 53.3% shared the same HPV type, showing moderate agreement, with a kappa index of 0.5. This finding supports the idea of circulation and recirculation of HPV among couples, perpetuating HPV in the sexually active population, rather than true recurrences of latent infections.